Analisis Strategi Pemasaran dan Persaingan: Studi Kasus pada UMKM Pemasaran Elektronik "Toko William Elektrik" di Bandar Jaya, Lampung Tengah, Provinsi Lampung - Daud, Syahril; Gellianta; Belinda, Sherliana; Arinda, Yeni (Jurnal EMT KITA, 2025)
This research aims to assist businesses such as William Elektrik in increasing sales and competitiveness through more effective marketing strategies. With increasing demand, competition in the electronics business sector is also getting tougher. Therefore, businesses need to apply SWOT analysis to understand the strengths, weaknesses, opportunities and threats that exist in their business. This research uses a qualitative approach with interview, observation, and documentation methods. The results of interviews with business owners show significant achievements and strategies used to maintain business success. The conclusion of this study shows that William Elektrik in Bandar Jaya, Central Lampung, has the potential to improve its competitiveness and sales through the application of SWOT analysis. Their main strength lies in their strategic location and customer loyalty, while the biggest weakness is their high operational costs. Opportunities for expansion can be found in the development of e-commerce and technical services, while threats come from intensifying competition in the electronics sector. By understanding and managing these factors, William Elektrik can formulate more effective marketing strategies. The findings can also serve as a reference for other businesses in designing marketing strategies.